Auditorium, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Meldrum, S.E. (1909)
S.E. Meldrum was one of the many amateur photographers allowed to photograph the grounds, buildings and exhibits of the exposition. By purchasing a day pass, an amateur photographer with a camera smaller then 6" x 8" was allowed to take unlimited pictures inside the exposition. The Auditorium was later the (Old) Meany Hall on the University of Washington campus. Handwritten in album: Two views of the Auditorium. PH Coll 61.8a To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number